Limitation of flow effect on passive sampling accuracy using POCIS with the PRC approach or o-DGT: A pilot-scale evaluation for pharmaceutical compounds. (May 2019) - Buzier, Rémy; Guibal, Robin; Lissalde, Sophie; Guibaud, Gilles
Abstract: Flow velocity is known to alter passive sampling accuracy. We investigated the POCIS (Polar Organic Chemical Integrative Sampler) with PRC (Performance Reference Compounds) approach and Diffusive Gradients in Thin Films samplers (o-DGT) to limit the effect of flow on the quantification accuracy of ten model pharmaceuticals compounds (0.16 ≤ log KOW ≤ 4.51). POCIS and o-DGT samplers were exposed for seven days in controlled pilot-scale (hundreds of liters) experiments under quiescent or flowing (2 < V < 18 cm s −1 ) conditions. Under flowing conditions, both POCIS-PRC and o-DGT efficiently limited the flow effect and led, in most cases, to biases within analytical uncertainty (20%). Under quiescent conditions, o-DGT performed accurately (bias < 30% for most compounds) whereas the PRC approach was unsuitable to improve upon the accuracy of POCIS (PRC was unable to desorb). Therefore, both approaches are helpful in limiting the effects of flow on accuracy, but only o-DGT is efficient in quiescent conditions. However, o-DGT currently suffers from poorer sensitivity compared to POCIS, but the future development of o-DGT devices with wider windows could overcome this limitation. Graphical abstract: Image 1 Highlights: POCIS with PRC (DIA-d5) allows limiting flow effect bias for some compounds. The PRC approach is of limited help in quiescent conditions. o-DGT allows limiting flow effect bias for some compounds.